Teaching Poverty in Social Work Classroom: A Sri Lankan Perspective - Subramaniam Jeevasuthan; Shamila Sivakumaran (Social Work and Society)
This chapter presents research exploring firsthand experience concerning teaching poverty in social work, challenges, and opportunities at the National Institute of Social Development (NISD), Sri Lanka. It is noteworthy that relevant reading materials and conceptual frameworks in teaching poverty with social work flavor are almost non-existent in Sri Lanka. Based on an intensive analysis of curricula, lecture notes, PowerPoint slides, question papers, exam papers and assignments, and formal discussions using a guideline with third-year social work students, educators, field agencies, and field supervisors, this research focuses on the unique challenges and opportunities to be considered by different stakeholders, affiliated to the NISD in various capacities. In practice, though faculty members and students get ample opportunities to teach and learn poverty education in social work, they recommended that conventional approaches be replaced with innovative ways to make the poverty subject more worthwhile and practical.